2022
DOI: 10.1007/s12144-021-02450-8
|View full text |Cite
|
Sign up to set email alerts
|

Does cognitive flexibility change the nature of the relationship between intolerance of uncertainty and psychological symptoms during the COVID-19 outbreak in Turkey?

Abstract: The COVID-19 pandemic has significantly affected the mental health of the general population worldwide. The study aimed to determine the associations of the intolerance of uncertainty (IU) and cognitive flexibility (CF) with a variety of psychological symptoms and to examine the impact of IU on psychological symptoms through the moderating role of CF. The Brief Symptom Inventory, Intolerance of Uncertainty Scale-12, and Cognitive Control and Flexibility Questionnaire were applied to a sample of 3004 adults liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…Cognitive flexibility plays a key role in reappraising situations (Dennis and Vander Wal, 2010;Inozu et al, 2022). It refers to people's mental ability to switch cognitive sets to adapt to changing environmental stimuli (Martin and Rubin, 1994;Dennis and Vander Wal, 2010).…”
Section: Moderating Role Of Cognitive Flexibilitymentioning
confidence: 99%
“…Cognitive flexibility plays a key role in reappraising situations (Dennis and Vander Wal, 2010;Inozu et al, 2022). It refers to people's mental ability to switch cognitive sets to adapt to changing environmental stimuli (Martin and Rubin, 1994;Dennis and Vander Wal, 2010).…”
Section: Moderating Role Of Cognitive Flexibilitymentioning
confidence: 99%
“…Emerging evidence has shown that the COVID-19 outbreak had a significant psychological impact on pregnant women (14)(15)(16). Temporary closure of public places, strict quarantine policies, and other measures were taken in various countries to prevent the spread of the virus (14,(17)(18)(19). There was a lot of available negative news information about COVID-19 online, which may increase distress and fears for the users.…”
Section: Introductionmentioning
confidence: 99%
“…In line with recent models of resilience and vulnerability processes in the pandemic context 21 , IU is expected to predict psychopathology, and ER difficulties and CCF are considered to modulate the impact of this factor on the trajectory of psychopathology. In line with these theoretical models, studies have vouched for a mediating effect of ER difficulties in the relationship between IU and psychopathology 23 , 67 , and another study has shown that different levels of CCF moderate the relation between IU and psychopathology 61 . As such, we had two main aims in the present study.…”
Section: Introductionmentioning
confidence: 87%
“…Very few studies have investigated the relationship between CCF and psychopathological symptomatology, with one study indicating that CCF was associated with pandemic-related anxiety 59 , and another study outside the pandemic context showing associations with depressive symptom severity 60 . Moreover, a first study examining the relationship between IU, CCF, and psychopathology found evidence for a moderating role of CCF in the relationship between IU and mental health difficulties 61 , indicating that greater levels of CCF supported adaptation to the uncertainty resulting from the COVID-19 pandemic, which further buffered increases in mental health problems. On the other hand, the relationship between CCF and ER difficulties has remained poorly studied as well.…”
Section: Introductionmentioning
confidence: 99%